Trend of a breeding population of Black kites Milvus migrans along the Po river in Turin (Italy) - Paolo Marotto (Rivista Italiana di Ornitologia - Research in Ornithology, 2016)
Black kites used the biggest waste dump of Turin for trophic purposes also during their reproductive months. After the dump closure there has been a sudden decrease in breeding pairs all over the area. During the following years the number of nests settled again however the small colonies trend was more scattered than before the landfill was closed.